Fluidités victoriennes - Béatrice Laurent (Cahiers Victoriens et Edouardiens)
The earth/water polarity seems to be one of the most important in the Victorian imagination for it asserts a gendered duality of the two elements.In 19th century British art, the fluid element is predominantly associated with women as is attested by popular subjects such as bathers, mermaids, naiads and drowned ladies. The culturally-constructed concept of a « natural » femininity defined by its fluidity and absorbency makes women the source at the same time as the container of vital fluids and serves the dominant discourse on gender as it conversely establishes masculine substantiality and impermeableness.This paper aims at examining a corpus of paintings illustrating the feminisation of water, and at suggesting interpretations in the light of contemporary, and sometimes fluctuating, scientific, medical or political discourses.